Pengaruh Lingkungan Sekolah terhadap Pembentukan Karakter Siswa: Penelitian - Irsandy Isnar; Sahiruddin; Haeril (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This research is a field research with a quantitative approach method that aims to determine the effect of the school environment on student character building. The population of this study were seventh grade students of MTs Yapit Taretta as many as 43 students with a full sampling sample. Data collection techniques in this study are observation, questionnaire (questionnaire) and documentation directly to the research location. Data analysis techniques using Descriptive Analysis. The data was processed with a validity test in the form of a questionnaire and reliability test. Then to answer the research hypothesis using simple linear regression formula and t test (partial). The results showed that the school environment affects the character building of MTs Yapit Taretta students. This means that the hypothesis H1 is accepted, because the value of t count> t table or 4.528> 1.6811 sig value of 0.001 <0.05.